Psychological characteristics of paralympic athletes’ self-realisation - Kokun, Oleg M.; Shamych, Oleksandr M. (Social Welfare: Interdisciplinary Approach, 2016)
The Paralympic sport has become an important tool for post-traumatic recovery, adaptation, integration and social inclusion of people with disabilities. Disabled people involvement into sports activities has important social implications not only for a person but also for society as a whole. Due to relative "youth" of the Paralympic sports, there are no enough studies aimed at creation of necessary scientific support not only for full-scale trainings and competitions of Paralympic athletes, but also for provision of full integration of Paralympians into society with the means of the Paralympic Sports, which is extremely important. High importance of psychological and socio-psychological research in this context is obvious. The article presents the results of our research aimed at identifying of common characteristics and factors of Paralympic athletes’ self-realization in order to promote the efficiency of trainings and competitions and full-scale integration into society